GAYA KEPEMIMPINAN DALAM MENINGKATKAN KINERJA PEGAWAI PADA ORGANISASI PUBLIK: STUDI LITERATUR TERSTRUKTUR - Jamil Febrian, Badri; Hinggil Permana; Abdul Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article synthesizes evidence on how leadership styles improve employee performance in public organizations. A structured literature review was conducted using 15 verified academic sources on transformational, transactional, participative, ethical, servant, change, and public leadership. Sources were selected through keyword searches and analyzed thematically by leadership mechanism, employee outcome, contextual condition, and implementation risk. Transformational leadership consistently supports contextual performance, commitment, innovation, and mission alignment through vision, inspirational communication, intellectual stimulation, and individualized support. Transactional leadership remains relevant for task clarity, discipline, monitoring, and contingent rewards, but is insufficient alone where innovation and adaptation are required. Participative, ethical, and servant practices strengthen trust, fairness, employee voice, and organizational citizenship behavior. In public organizations, these effects operate through mission valence, public service motivation, leader-employee relationship quality, and commitment to change. An effective approach integrates transformational direction, participative decision-making, ethical conduct, and proportional transactional control.